The relationship of use of injection contraception with age menopause in the sub-district of Gung Negeri Kabanjahe - Alfrianne (Science Midwifery, 2023)
The incidence of menopause in women aged 40-58 years which can occur early or late. One of the factors that influence menopausal women's entry into hormonal contraception. The aim is to determine the relationship between the use of injectable birth control and the age of menopause in the Gung Negeri Kabanjahe sub-district. This study was a cross-sectional design with an analytic survey approach. The research has conducted a total of 105 respondents using the chi square statistical test. The results of the study were 42 respondents (66.7%) who used injectable contraceptives < 3 years experienced menopause at the age of < 49 years, while 21 respondents (33.3%) experienced menopause at the age of ≥ 49 years. While the use of injection contraception ≥ 3 years experienced menopause at the age of <49 years by 18 respondents (42.9%), menopausal age ≥ 49 years by 24 respondents (57.1%). The results of statistical data using the chi-square test found that p value = 0.016 <0.05 indicating that there was a relationship between the use of DMPA injection contraception (Depo Medroxy Progesterone Acetate) and the incidence of menopause in the Gung Negeri Kabanjahe sub-district. The conclusion of this study is that there is a relationship between the use of DMPA injection contraception (Depo Medroxy Progesterone Acetate) and the incidence menopause in the Gung Negeri Kabanjahe sub-district which has a significant level of closeness.